2019
DOI: 10.1071/hc19012
|View full text |Cite
|
Sign up to set email alerts
|

Green diabetes mellitus: a pilot project

Abstract: INTRODUCTIONMost of approximately 422 million people globally have diabetes mellitus use sharps for glucose monitoring. Many adults with diabetes are unaware of safe disposal methods, posing a risk of injury or potential infection to others. AIMTo determine how adults with diabetes dispose of diabetes care-related waste and to assess changes in their disposal habits after receiving brief targeted education during medical visits. METHODSAmbulatory adults with diabetes (aged ≥18 years) were enrolled during their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…To the best of our knowledge, there was no data available about home disposal practices of medical sharps in the Portuguese diabetic population, as in many other countries 20. We found clear evidence of inadequate disposal of medical sharps among these patients, findings that are corroborated by studies in the same scope conducted in other countries, which reported household bin disposal of medical sharps ranging from 33% to 92%,3 7 8 10 13 15 17 18 21–28 a common problem worldwide 9. Our results show that over two-thirds of diabetic patients discard sharps directly into common household bins.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To the best of our knowledge, there was no data available about home disposal practices of medical sharps in the Portuguese diabetic population, as in many other countries 20. We found clear evidence of inadequate disposal of medical sharps among these patients, findings that are corroborated by studies in the same scope conducted in other countries, which reported household bin disposal of medical sharps ranging from 33% to 92%,3 7 8 10 13 15 17 18 21–28 a common problem worldwide 9. Our results show that over two-thirds of diabetic patients discard sharps directly into common household bins.…”
Section: Discussionsupporting
confidence: 76%
“…However, from the beginning of the therapeutic plan, it is necessary to provide education to patients and their families about the importance of proper disposal of sharps, not neglecting the education of healthcare professionals 20. Even though educating patients might be challenging, a broad and improved knowledge on safe sharps disposal is required, as there is evidence that patients are more likely to dispose of sharps properly if advised by healthcare providers, especially if there is ongoing support from the healthcare team 18 21 30…”
Section: Discussionmentioning
confidence: 99%
“…Considering different requirements and constraints, this study proposes a system to make decisions based on different conditions. This research work mainly focuses on the development of a reliable Nutrition Diet Expert System (NDES) based on nutritional recommendations for diabetes patients that will be useful specifically for HCPs and will enable them to monitor the patients' health in hospitals and at home [5]. Health monitoring systems are one of the major advancements in the information technology (IT) field with the market of wearable devices worldwide producing revenue of around $26 B which is expected to increase to $34 B in 2021 [6].…”
Section: Introductionmentioning
confidence: 99%
“…9 On more clinical matters, we have a short report reminds readers that some patients with diabetes face obstacles in disposing of their diabetes-related 'sharps'. 10 Two qualitative research reports explore issues relating to how patients feel about doctors disclosing their own health problems 11 and how Asian immigrant gay men regard pre-exposure prophylaxis to protect them from HIV. 12 Wrapping up the issue we have the Potion or Poison and Cochrane Corner columns and two case reports, one highlighting a rare condition 13 and the other condition that is difficult to diagnose: both from primary care.…”
mentioning
confidence: 99%